2016
DOI: 10.1177/1971400916665382
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of diffusion tensor imaging metrics in differentiating low-grade from high-grade gliomas

Abstract: We conclude that the combination of MD of the solid tumoral part and FA of the peri-tumoral region is a noninvasive method to differentiate low-grade from high-grade gliomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
67
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(72 citation statements)
references
References 38 publications
4
67
0
1
Order By: Relevance
“…DTI takes the advantage of diffusion of water in brain tissue within three main directions, which is decreased perpendicularly to the myelin sheaths and cell membranes of white-matter axons [6].…”
Section: Discussionmentioning
confidence: 99%
“…DTI takes the advantage of diffusion of water in brain tissue within three main directions, which is decreased perpendicularly to the myelin sheaths and cell membranes of white-matter axons [6].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies used subjective placement of ROIs surrounding the tumor to examine FA and/or MD (3, 10, 12, 15, 16, 21, 23, 2528). Several studies have employed experts to manually draw a perimeter around the tumor (47, 11, 14, 19, 22, 24, 29).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have employed experts to manually draw a perimeter around the tumor (47, 11, 14, 19, 22, 24, 29). In addition, the majority of previous studies were limited by small numbers of patients included in the studies (37, 10, 11, 1416, 21, 22, 2426, 28, 29). …”
Section: Introductionmentioning
confidence: 99%
“…19 DTI has been reported to distinguish high-from low-grade gliomas, 20 and in particular the MD measured in the tumor bulk achieved an accuracy of 91.4%. 21 However, in studies comparing multiple modalities, measures of perfusion were superior for grading, and a multimodality algorithm was best. 22 While DTI makes the assumption that water diffusion assumes a Gaussian distribution, diffusion kurtosis imaging (DKI) accounts for the fact that the highly organized architecture of brain parenchyma results in a non-Gaussian distribution of water diffusion.…”
Section: Diagnostic Clues In Standard Mrimentioning
confidence: 99%
“…For example, study of 31 patients demonstrated that DTI could reliably be used to predict invasion into the corpus callosum . DTI has been reported to distinguish high‐ from low‐grade gliomas, and in particular the MD measured in the tumor bulk achieved an accuracy of 91.4% . However, in studies comparing multiple modalities, measures of perfusion were superior for grading, and a multimodality algorithm was best .…”
Section: Introductionmentioning
confidence: 99%